On thin ice: Linking elevation and long‐term losses of lake ice cover. Issue 2 (5th February 2021) - Christianson, Kyle R.; Loria, Kelly A.; Blanken, Peter D.; Caine, Nel; Johnson, Pieter T. J.
Abstract: Despite long‐term analyses of lake ice phenology globally, comparatively little is known about high‐elevation lakes, for which climate shifts are thought to be occurring faster than at lower elevations. Using a 36‐yr dataset (1983–2018) on alpine lakes (> 3000 m ASL) from the Green Lakes Valley, Colorado (GLV), we found that ice‐cover duration decreased by an average of ~ 24 d, due to both earlier ice‐off (9 d) and especially later ice‐on (15 d). Spring ice thickness also decreased by 0.88 cm yr −1 . By comparison, ice‐cover duration in the GLV is decreasing ~ 50% faster than for Northern Hemisphere lakes ( n = 215), which translates to an increase in open water duration ~ 2.5 times more in the GLV than the average of the Northern Hemisphere. Our analytical comparison demonstrated more rapid trends in this alpine region compared to lakes more broadly, and especially emphasized the influence of elevation on lake ice phenology.